The effects of using collocations in teaching English vocabulary for 11th – grade students at Son Tay high school . M.A. Thesis Linguistics: 60 1 - Hoàng, Thị Dung (ĐHNN, 2017)
This paper reports a quasi -experimental research that aimed to address the impacts of collocation teaching on grade 11 students‟ vocabulary improvements. Data for the study including two proficiency tests and a follow - up questionnaire were collected from 92 students at Son Tay High school. In this study, 46 students who followed the conventional vocabulary teaching methods belong to control group, and 46 others participated in experimental group in which they are exposed to different strategies related to collocation learning. The scores taken from the two tests were analyzed using the Statistical Package for the Social Sciences (SPSS) for Windows version 20.0 software package. The results show that English collocation teaching has improved the students‟ vocabulary learning. The findings from the questionnaire indicate that students also have positive attitude towards the new vocabulary teaching method. They have become well aware of the collocations‟ importance in language learning. And they have also developed the habit of learning collocations independently outside the classroom. The findings from the tests and the questionn aire support each other to affirm the undeniable positive effects of the collocation teaching. Recommendations for students‟ English vocabulary improvements and suggestions for further studies are provided on the basis of the research findings as well.